Analysis Of The Levels Of Vitamin C In Fruit Green Grapes (Vitis vinifera L.) With A Variation Of The Old Post-Harvest Storage - Astria, Linda Yuniar; Yusuf, Bohari; Alimuddin, Alimuddin (JURNAL ATOMIK, 2018)
A research on the analysis of the levels of vitamin C in fruit green grapes (Vitis vinifera L.) with a variation of the old post-harvest storage. The study was conducted with a variety of post-harvest storage time for 7 days at room temperature and coolant temperature, and test level of vitamin C used is the titration method iodimetri were then analyzed using independent t-test. The results showed that there was no effect of storage time on the vitamin C content of green grapes on storage at room temperature and coolant temperature. The highest levels of vitamin C contained in the storage day 5 the coolant temperature is 15.37 mg/g sample.